A Critical Study of Adolescent Social Interactions from Ibn Miskawaih's Perspective - Imam Fadaah; Irwan Supriadin; Junaidin Junaidin (Prodi PAI STIT Sunan Giri Bima, 2025)
This study aims to analyze the social life of adolescents in Bima from the perspective of Ibn Miskawaih and its relevance to the concept of Maja Labo Dahu . With the increase in negative behavior among adolescents, such as delinquency, fighting, and drug abuse, this study focuses on how moral values can be applied to improve the social life of adolescents in Bima. This study uses Literature Study research based on the Indonesian translation of the work by Hidayat Helmi